PENGARUH HAMBATAN SAMPING TERHADAP KINERJA BUNDARAN JALAN SUTAN SYAHRIR – JALAN SELAYAR – JALAN PROF. DR. MUH. YAMIN – JALAN DR. SUTOMO DI KOTA PONTIANAK - Yoan Retnowati; Komala Erwan; - Said (JeLAST : Jurnal Teknik Kelautan , PWK , Sipil, dan Tambang, 2016)
The purpose of this study was to analyze due to the influence of the side barriers on the performance of the roundabout by the Indonesian Highway Capacity Manual (MKJI, 1997). Results from the study showed that the largest flows occurred on Monday afternoon hours of 16:00 to 5:00 p.m. GMT value Degree of Saturation (DS) is the arm (AB) 0.43, (BC) 1.16, (CD) 0.50, (DA ) 0.50. Delay traffic roundabout average = 37.071 sec / smp, delay roundabout = 41.071 sec / smp. Opportunities roundabout Queues at least 57% and a maximum of 100%. While the results of the average weighting factor aside barriers between 58.3 to 315 events, this shows that the side friction factor occurred relatih still low. And for the overall performance level Roundabout affected by traffic flow at peak hours of the morning (6:00 to 8:00 a.m.), during peak hours (11:00 to 13:00) and evening peak hours (4:00 p.m. to 5:00 p.m.) in which the degree of saturation that occurs between 0.525 to 1.100. From the results of these conditions Roundabout New Town was not able to serve existing traffic flow. Kota Baru roundabout performance requires a traffic management, so as to serve traffic flow optimally.   Key words: roundabouts, side barrier and MKJI.